2009
DOI: 10.1055/s-0029-1245105
|View full text |Cite
|
Sign up to set email alerts
|

The Multifactorial Etiology of Inhibitor Development in Hemophilia: Genetics and Environment

Abstract: The most important complication in the treatment of hemophilia A patients today is the development of inhibitory antibodies against infused factor VIII (FVIII). Inhibitor development is caused by a complex interplay between both genetic and environmental factors. The risk of developing inhibitors is greatest in previously untreated patients with severe hemophilia A. Several genetic factors, such as a positive family history of inhibitors, ethnicity, FVIII genotype, and certain polymorphisms in immune modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 82 publications
(107 reference statements)
0
103
0
Order By: Relevance
“…[32][33][34][35] A possibly increased inhibitor risk was seen for subjects with HLA-DR15 and the H2 haplotype (Table 5), but this was not seen for those with peak titers $5 BU/mL (supplemental Table 3). Future studies will evaluate additional genetic and environmental factors 34,[36][37][38] that influence race-associated differences in inhibitor risk.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] A possibly increased inhibitor risk was seen for subjects with HLA-DR15 and the H2 haplotype (Table 5), but this was not seen for those with peak titers $5 BU/mL (supplemental Table 3). Future studies will evaluate additional genetic and environmental factors 34,[36][37][38] that influence race-associated differences in inhibitor risk.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Studies on genetic determinants of inhibitor development have indicated numerous genetic markers, such as the type of causative F8 gene mutation, single nucleotide polymorphisms (SNPs) in the HLA locus and in other immunoregulatory genes, ethnic background, and family history of inhibitors, to be involved in the etiology of this treatment complication.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for early inhibitor development include a family history of inhibitors, nonwhite ethnicity, factor VIII mutation, and intense factor VIII replacement therapy. [1][2][3] It is usually assumed that most factor VIII inhibitors arise after relatively few factor VIII exposure days, early in the patient's life, and that the risk of inhibitor development is subsequently very low. [4][5][6] Reports to the United Kingdom National Hemophilia Database (NHD) suggest that new inhibitors may present throughout life in patients with severe hemophilia and that this risk increases in older patients.…”
Section: Introductionmentioning
confidence: 99%